Millennium Development Goals critical perspective from Central Asia - Jaganjacová, Nina (2012)
World is diverse and so is the life standard of people in all the countries. Central Asia countries have nearly same history, culture and nature, but different problems in development, environment, health or trade. Since none of these countries reaches level of living desired by The United Nations, Millennium Development Goals are created to help improving development in all the undeveloped countries. Goals of submitted thesis are to evaluate and show Millennium Development Goals in Central Asia region specifically in Kazakhstan, and to critically valorize them based on interviews with actively participating employees of international institutions currently working in Kazakhstan and on survey of non-involved European citizens.